Evaluasi Dampak Ekonomi dan Sosial Perkebunan Kelapa Sawit Di Kawasan Hutan Terhadap Kesejahteraan Masyarakat Di Kabupaten Batanghari (2020–2025) - Asna Nengsih; M.Ridwansyah; Zainul Bahri; Siti Hodijah; Nurhayani (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to evaluate the economic and social impacts of oil palm plantations in forest areas on community welfare in Batanghari Regency during the period 2020–2025. A quantitative approach was used to measure objective indicators such as income and access to facilities, as well as community perceptions regarding economic benefits. Data were collected through questionnaires and interviews from approximately 100 households using a stratified random sampling technique. The results indicate that land area, community participation, land legality, and market access have a positive influence on welfare, while environmental factors and management sustainability are important concerns. This study recommends policies that balance economic benefits and environmental preservation for sustainable development.